Assessment of the effectiveness of electronic gatekeeping as a utilization management tool at Groote Schuur Hospital - Bosman, Michelle (Department of Clinical Laboratory Science, 2019)
BACKGROUND: Utilization management ensures the appropriateness of laboratory testing by reducing the performance of tests which can be reasonably avoided with no adverse effects for the patient. Electronic gatekeeping, a utilization management tool, was introduced at Groote Schuur in 2010. Criteria were based on the minimum retesting interval, healthcare location, level of experience and discipline of the requesting clinician and specific ICD-10 codes. METHODS: A retrospective observational study assessing the effectiveness of electronic gatekeeping at Groote Schuur Hospital (Cape Town, South Africa), by comparing the test request volumes by using absolute test numbers and pre-defined ratios in the year prior to gatekeeping, to the two years following implementation. A secondary aim is to apply selected ratios to the other national academic hospitals to determine the potential for cost saving. RESULTS: At the medical wards of Groote Schuur Hospital there was an overall decrease in number and cost of tests of 24% per inpatient day for 2011. The most dramatic difference in cost is seen for chloride (91%) followed by HbA1c (90%), FT3 (89%) and CRP (82%). The application of ratios to Groote Schuur Hospital show a decrease in 2011 in all ratios apart from PCT: FBC+WCC (0.003 vs 0.002) and Mg: Ca (0.86 vs 0.84). AST: ALT remained the same at 0.55. This suggests overall effectiveness of the eGK rules although there is ongoing panel requesting. If the GSH eGK rules were to be applied at all other national academic hospitals, it could translate into a potential cost saving of $13 411 873.96 (R103 196 838.80) per annum. CONCLUSIONS: Electronic gatekeeping is an effective utilization management tool at Groote Schuur Hospital. It is relatively easy to implement and manage, and when combined with additional tools has the potential to result in larger reductions of unnecessary tests, cost savings and improved patient outcome.